New records of the Saber Anchovy Stolephorus acinaces (Teleostei: Clupeiformes: Engraulidae) from Vietnam - Hata, Harutaka; Lavoué, Sébastien; Quan, Nguyen Van; Motomura, Hiroyuki (Vietnam Journal of Marine Science and Technology, 2025)
Four specimens of Stolephorus acinaces Hata, Lavoué and Motomura, 2020 (previously known only from the type specimens collected from the northern coast of Borneo) were collected from southern Vietnam, and their identification confirmed by analysis of the cytochrome oxidase subunit I (COI) gene. The specimens represent the northernmost records of the species, which is redescribed, including a fresh color description for the first time, and are suggestive of a wide distribution in the southern Bien Dong Sea.